ANALISIS WACANA HATE SPEECH DALAM LIVE STREAMING YOUTUBE LIGAGAME E-SPORTS TV - Thomas Dewo Ayudya; Bonardo Marulitua Aritonang; Ester Krisnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Technological development on online communication was creating various communication on the internet, one of them is live streaming features on Youtube. Communication variation on the internet still has a problem, one of them is the existence of hate speech on the comment section in live streaming Youtube of Ligagame eSports TV Youtube Channel. Theory of Discourse from Ernesto Laclau and Chantal Mouffe become guidelines to analyze the discourse formed from caster so that appeared hate speech from audience comment, which that hate speech divided into some type of cyberbullying. To analyze that, the researcher does observation or directly observe when live streaming been held and interview part of Kominfo Salatiga as a data triangulation. The result of the research shows that delivery like anything brought by the caster in streaming would still bring up hate speech comment from the audience, and a caster can react with the reply the hate speech argument from the audience, offer a solution to stop hate speech from appearing, or just ignore that comment.Keywords: Hate Speech, Caster, Discourse, Youtube, Cyberbullying.